(untitled) (TAMADDUN NURI JURNALI, 2024)
This article talks about innovations related to the world of imagination and thought of Alisher Navoi. It is emphasized that Alisher Navoi’s works are the basis for great scientific achievements, and this is a direct product of Navoi’s artistic thinking.